Design of pressure vessels using shape optimization: An integrated approach - Carbonari, R.C.; Muñoz-Rojas, P.A.; Andrade, E.Q.; Paulino, G.H.; Nishimoto, K.; Silva, E.C.N. (The International journal of pressure vessels and piping, 2011)
Previous papers related to the optimization of pressure vessels have considered the optimization of the nozzle independently from the dished end. This approach generates problems such as thickness variation from nozzle to dished end (coupling cylindrical region) and, as a consequence, it reduces the optimality of the final result which may also be influenced by the boundary conditions. Thus, this work discusses shape optimization of axisymmetric pressure vessels considering an integrated approach in which the entire pressure vessel model is used in conjunction with a multi-objective function that aims to minimize the von-Mises mechanical stress from nozzle to head. Representative examples are examined and solutions obtained for the entire vessel considering temperature and pressure loading. It is noteworthy that different shapes from the usual ones are obtained. Even though such different shapes may not be profitable considering present manufacturing processes, they may be competitive for future manufacturing technologies, and contribute to a better understanding of the actual influence of shape in the behavior of pressure vessels. ► Shape optimization of entire pressure vessel considering an integrated approach. ► By increasing the number of spline knots, the convergence stability is improved. ► The null angle condition gives lower stress values resulting in a better design. ► The cylinder stresses are very sensitive to the cylinder length. ► The shape optimization of the entire vessel must be considered for cylinder length.